(untitled) (Revista Sistemas de Producción Agroecológicos, 2011)
Cuban livestock, like the rest of Latin America needs innovative technologies that are sustainable in environmental, economic and technical productive, considering the definition of sustainable development provided by FAO (1990). Some of these technologies are silvopastoral systems and on the production, processing and conservation of fodder plant seed, developed by the Experimental Station of Pastures and Forages "Indio Hatuey" for livestock. Likewise, Cuba is a country with scarce energy resources and is forced to import nearly all the oil it needs to maintain its production. Therefore, a way for the country is the development of sustainable livestock production systems such as those mentioned above, which depend on local resources available. The country spends more than 2 500 000 hectares of pasture for livestock, but its low productivity is a problem that needs solving to produce enough milk and meat for a population that has been steadily increasing. Improved pastures in the mid-80’s, reaching over 50% of the agricultural area of ​​livestock in the country, but currently only reach 19%. 58% is covered with natural grasses and by weeds, among which stand the smell and marabou, covering 39% of the total agricultural area of ​​grassland. No less important is also the high percentage who now occupy the espartillo and caguazo. At present, the soil fertility decreases and livestock as a result, biomass production of grasslands has declined and pastures have been degraded. This has serious consequences for the cattle industry, by reducing meat and milk yields and increased costs of animal production. The causes of this decline are many, among which include overgrazing, declining soil fertility, poor role played by herbaceous legumes in pastures, weed invasion, drought and erosion. The renewal and recovery of pastures should be the fundamental task to provide short to medium term, of a food base in sufficient quantity and quality to sustain the mass cattle and thus contribute effectively to the recovery livestock.